The Construction of Discrimination Against the Shi'a Community in Sampang, Madura: A Religious Structural Violence Perspective - Achmad, Mukhsin (UIN Sunan Kalijaga, 2021)
Abstrak: Paper ini mengkaji kekerasan terhadap komunitas Syiah di Sampang, Madura yang menjadi isu laten dan sangat mungkin akan terjadi di tempat dan waktu yang lain. Paper ini mengeksplorasi produksi media dalam masyarakat yang mengkonstruksi dan mendiskriminasi minoritas agama serta peran otoritas keagamaan di Sampang, Madura. Paper ini didasarkan pada penelitian kualitatif melalui studi kepustakaan dan empiris dengan memanfaatkan teori Johan Galtung dan memadukannya dengan analisis wacana kritis Norman Fairclough. Paper ini menemukan bahwa wacana terhadap Syi’ah sebagai sistem kepercayaan sesat di Sampang Madura diproduksi oleh media. Otoritas agama mengambil cukup peran untuk mendukung dan menyebarkan wacana ini ke berbagai kelompok sosial. Dari kajian yang telah dilakukan juga ditemukan bahwa terdapat kekerasan kultural dan struktural terhadap komunitas Syi’ah di Sampang Madura dalam wujud diskriminasi, intimidasi dan kekerasan.Abstract: The paper examines the violence against the Shi'a community in Sampang, Madura. It is a latent issue and is highly likely to occur in different contexts. The paper also explores media production in the society that constructs and discriminates against religious minorities and the role of religious authorities in Sampang, Madura. The paper is mainly based on qualitative research through literature and empirical studies, utilizing Johan Galtung's triangulation of violence theory and Norman Fairclough's critical discourse analysis. The results indicate that the discourse on Shi'a as a dissenting group in Sampang, Madura, is produced by the media. Religious authorities play an essential role in supporting and spreading the discourse to various social groups. The study also highlights cultural and structural acts of violence to the Shi'a community in Sampang through discrimination, intimidation, and violence.